PENGARUH LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PENGELOLAAN KEUANGAN DAN INKLUSI KEUANGAN SEBAGAI VARIABEL INTERVENING DI MASA PANDEMI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Islamia, Alfia; Wiryaningtyas, Dwi Perwitasari; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out financial literacy has a significant effect on financial inclusion, financial attitudes have a significant effect on financial inclusion, financial literacy has a significant effect on financial management, financial attitudes have a significant effect on financial management, financial inclusion has a significant effect on financial management, financial literacy significant effect on financial management through financial inclusion, financial attitude has a significant effect on financial management through financial inclusion. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) Based on the results of the study, it is known that financial literacy has a positive and significant effect on financial inclusion, financial attitudes have a positive and significant effect on financial inclusion, financial literacy has a positive and significant effect on financial management, financial attitudes have a positive and significant effect on financial management, financial inclusion has a positive and significant impact on financial management. significant on financial management, financial inclusion has a positive but not significant effect on financial management through financial inclusion, financial attitudes have a positive and significant effect on financial management through financial inclusion.